Salafi dan Stigma Sesat-Radikal - Slamet Muliono Redjosari (Islamica: Jurnal Studi Keislaman, 2019)
This article describes the dynamics of da‘wa movement of Salafis and their response to its stigmatization as being heretical and radical. The phenomenon of radical movements with their terrorist actions shapes the stigma of being radical to the Salafis. The spread and acceleration of the Salafi movement have put the da‘wa of the traditionalists in trouble. The stigma of Salafis as being radical and heretical results in the resistance against the Salafis to stop their da‘wa in many places. The stigmatization of the Salafis as being radical and intolerant drives the Salafis to show their identity as unidentical with the stigmatization. A number of persecutions towards the Salafis is the implication of this stigma. This article has resulted from interviews with Salafi figures and dā‘īs who felt annoyed with the stigmatization. The appearance of Salafis which resembles those stigmatized as radicals lead to the emergence of public opinion that the Salafis are radical, while on the contrary, this article finds that the Salafis in fact fight against radical thoughts that lead to radical and terrorist actions.